LigB subunit vaccine confers sterile immunity against challenge in the hamster model of leptospirosis. - Neida L Conrad; Flávia W Cruz McBride; Jéssica D Souza; Marcelle M Silveira; Samuel Félix; Karla S Mendonça; Cleiton S Santos; Daniel A Athanazio; Marco A Medeiros; Mitermayer G Reis; Odir A Dellagostin; Alan J A McBride (Public Library of Science (PLoS), 2017)
Neglected tropical diseases, including zoonoses such as leptospirosis, have a major impact on rural and poor urban communities, particularly in developing countries. This has led to major investment in antipoverty vaccines that focus on diseases that influence public health and thereby productivity. While the true, global, impact of leptospirosis is unknown due to the lack of adequate laboratory diagnosis, the WHO estimates that incidence has doubled over the last 15 years to over 1 million cases that require hospitalization every year. Leptospirosis is caused by pathogenic Leptospira spp. and is spread through direct contact with infected animals, their urine or contaminated water and soil. Inactivated leptospirosis vaccines, or bacterins, are approved in only a handful of countries due to the lack of heterologous protection (there are > 250 pathogenic Leptospira serovars) and the serious side-effects associated with vaccination. Currently, research has focused on recombinant vaccines, a possible solution to these problems. However, due to a lack of standardised animal models, rigorous statistical analysis and poor reproducibility, this approach has met with limited success. We evaluated a subunit vaccine preparation, based on a conserved region of the leptospiral immunoglobulin-like B protein (LigB(131-645)) and aluminium hydroxide (AH), in the hamster model of leptospirosis. The vaccine conferred significant protection (80.0-100%, P < 0.05) against mortality in vaccinated animals in seven independent experiments. The efficacy of the LigB(131-645)/AH vaccine ranged from 87.5-100% and we observed sterile immunity (87.5-100%) among the vaccinated survivors. Significant levels of IgM and IgG were induced among vaccinated animals, although they did not correlate with immunity. A mixed IgG1/IgG2 subclass profile was associated with the subunit vaccine, compared to the predominant IgG2 profile seen in bacterin vaccinated hamsters. These findings suggest that LigB(131-645) is a vaccine candidate against leptospirosis with potential ramifications to public and veterinary health.